Encouraging dentists as agents of change in the fight against tobacco in Malaysia: An example of a dentist-psychiatrist collaborative effort - Siddiq AN, Amer; NA, Yahya; Aiza H, Nazariah; IZ, Zul-Izzat; AR, Rusdi; Muhsin AZ, Muhammad; AR, Aisah; Z, Hazli; Zurani MHR, Noor; Kadir R, Abdul; H, Hussain (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2011)
Dentist has long been recognized as a formal health profession. Health professionals have an important role to play in the fight against tobacco. Smoking tobacco is dangerous because it related disease and also due to it being labeled as a gateway to illicit drug abuse. As individuals, the dentist can help educate the population, as community members they can support anti-smoking policies and at a societal level, they can influence national and global tobacco control efforts. The associations between tobacco use and diseases affecting the oral cavity, such as periodontal disease and cancer, are now well recognized. This has lead to proposals from some members of the profession that members of the dental team should provide smoking cessation services. Before exploring effective ways to help smokers quit, it is important to understand the nature of the addictive process and how it affects both nicotine use and cessation attempts. The potential influence of dentists as agents of change is clear from even a brief consideration of the nature and conditions of the dentist-patient relationship. The dental practice setting provides a unique opportunity to assist tobacco users in achieving tobacco abstinence. The role of psychiatrists to support the effort, therefore, becomes all the more important.